Pengaruh Promosi Influencer Di Social Media Tiktok Terhadap Minat Beli Bagi Generasi Z - Jerryko Reynaldi Putra; Sumadi Sumadi (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
This study aims to analyze the effect of influencer appearance, trust, and influencer content on purchase intention and the mediating role of brand attitudes in Indonesia with Tiktok social media. The analysis used uses the SPSS application program and SmartPLS modeling. This research was conducted throughout Indonesia. This research is causality research with variables including three independent variables, namely influencer characteristics, trust in influencers, and credibility of post content, and dependent variables including brand attitude and purchase intention. The population used is generation Z, which knows and uses Tiktok social media. The sampling technique used was nonprobability sampling, namely purposive sampling. The number of samples used was 197, and they were analyzed using SEM SmartPLS. The results of the data analysis show that influencer appearance has a negative and insignificant effect on brand attitude. Influencer appearance has a positive and significant effect on purchase intention. Trust has a positive and significant effect on brand attitudes. Influencer content has a positive and significant effect on brand attitude.